THE ANALYSIS OF TEACHER TALK AND LEARNER TALK IN THE CLASSROOM INTERACTION: A Descriptive Study at 1st Grade of Senior High School in Bandung - Nurhasanah (2013)
The research entitled The Analysis of Teacher Talk and Learner Talk in the Classroom Interaction: A Descriptive Study at 1st Grade of Senior High School in Bandung aims at describing types of teacher talk and learner talk occur in classroom interaction, and finding the advantages and disadvantages of teacher talk and learner talk. This research used descriptive qualitative design. It was at first grade of senior high school in Bandung. The research involves one class of first grade students of a senior high school in Bandung as participants. The data were obtained through video recorded and interview. The data were analyzed by applying Flander's Interaction Analysis Categories (FIAC) focusing on types of teacher talk and learner talk. Findings were descriptive analyses with transcribing, coding, and analyzing. The result shows that all of teacher talk categories revealed that asking question and lecturing was found as the most frequently used. In terms of learner talk, learner talk response and initiation were revealed in this research. According to the results, it can be concluded that teacher talk and learners talk categories are important part in classroom interaction and there are found more advantages rather than the disadvantages. In addition, the factor that influenced types of teacher talk and learner talk was also supported by students' response in the interviews. This research is expected to give a contribution to the teaching English especially in classroom interaction. Key words: Teacher talk, Learner talk, classroom interaction, teacher's role, interaction analysis. Penelitian ini berjudul The Analysis of Teacher Talk and Learner Talk in the Classroom Interaction: A Descriptive Study at 1st Grade of Senior High School in Bandung. Tujuan penelitian ini adalah untuk mendeskripsikan tipe dari teacher talk dan learner talk dalam interaksi yang terjadi didalam kelas dan menemukan keuntungan dan kerugian dari teacher talk dan learner talk. Penelitian ini menggunakan design descriptive kualitative. Instrument dalam pengumpulan data menggunakan video recording dan interview. Partisipan dalam penelitian ini adalah satu kelas siswa SMA kelas X. Analisis data menggunakan teori Flander's Interaction Analysis Categories (FIAC) focus terhadap jenis dari teacher talk dan learner talk. Dalam menganalisis hasil penelitian menggunakan beberapa tahap, yaitu transcribing, coding, categorizing dan analyzing. Dalam hasil penelitian menunjukkan bahwa bahwa kategori dari teacher talk yang paling dominan digunakan oleh guru adalah asks question dan lecturing. Kategori dari learner talk yang paling sering digunakan oleh siswa adalah learner talk-response. Dalam penelitian ini ditemukan bahwa lebih banyak keuntungan dibandingkan kerugiannya. Berdasarkan hasil dari penelitian ini dapat disimpulkan bahwa kategori dari teacher talk dan learner talk sangat penting dalam meningkatkan interaksi didalam kelas. Penelitian ini diharapkan untuk memberikan kontribusi dalam proses belajar mengajar bahasa Inggris khususnya pada interaksi di dalam kelas. Kata kunci: teacher talk, learner talk, classroom interaction, teacher's role, dan interaction analysis.